The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.annemergmed.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hospital Triage of Older Adults With Head Injury: A Retrospective Study of the Effect of Adding “Anticoagulation or Antiplatelet Medication Use” as a Criterion

Abstract: Study Objective Field triage guidelines recommend EMS providers consider transport of head injured older adults with anticoagulation use to trauma centers. However the triage patterns and the incidence of intracranial hemorrhage or neurosurgery in these patients are unknown. Our objective was to describe the characteristics and outcomes of older adults with head trauma transported by EMS, particularly in patients that do not meet physiological, anatomical, or mechanism of injury (Step 1-3) field triage criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…7 Prior studies have also shown that current field triage guidelines are not accurate in predicting trauma center need in this population. [8][9][10]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Prior studies have also shown that current field triage guidelines are not accurate in predicting trauma center need in this population. [8][9][10]…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with head injury often have minor mechanisms of injury, such as falls from standing height, yet have significant traumatic intracranial hemorrhage . Prior studies have also shown that current field triage guidelines are not accurate in predicting trauma center need in this population …”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have pointed out that the use of standard triage criteria is followed by undertriage of patients over the age of 60 1 11 12 14 28 36. Several studies have tried to demonstrate an effect on undertriage and outcome by redefining trauma criteria for the elderly 13 37 38. Brown et al found that substituting SBP of less than 110 mm Hg with the current 90 mm Hg in patients older than 65 achieves a larger reduction in undertriage than increase in overtriage and the risk for mortality is similar in these groups 39.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that prospectively compares the incidence of tICH in head-injured older adults transported by EMS with and without anticoagulation. Prior studies related to this topic have been limited by their retrospective design, 9,10,18,29 lack of patients taking direct oral anticoagulants, 9,10,18,29 and lack of comparator group (i.e., patients not taking anticoagulant or antiplatelet agents). 9,18,28,30 Given the aging population in the United States and the increasing proportion of injured older adults being transported by EMS agencies and evaluated in EDs, this is a high priority area of study for pre-hospital and ED providers.…”
Section: Discussionmentioning
confidence: 99%